2020
DOI: 10.4102/sajce.v10i1.820
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening comprehensive sexuality education in the curriculum for the early grades

Abstract: This article aims to strengthen the comprehensive sexuality education (CSE) curriculum for the early grades (Grade R-3, children between the ages of 6 and 8 years) and to gain an understanding of teachers' knowledge and understanding of CSE and its links to the Curriculum and Assessment Policy Statement (CAPS): Life Skills. Background:The continuing high rate of child abuse and sexual violence has highlighted the need for a focused intervention in the form of educating young learners on sexual risks and protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The schools can also create collaboration with Ministry of Education (MOE), Ministry of Health (MOH) and non-governmental organizations by planning and organizing campaigns and workshops for the preparation of teaching materials/aid kits, and enhance understanding and confidence of teachers, parents and children about the sexuality topic (Hasmadi et al, 2022). In addition, Venketsamy & Kinear (2020) viewed that teachers need to be empowered with knowledge and understanding of the sexuality education content so that students are more sensitive to their surroundings, make appropriate decisions, aware of sexual abuse and communicate effectively when they experience sexual abuse. Balter et al (2016) claimed that support from school administrators can increase the motivation of early childhood education teachers to talk explicitly with children about sexuality.…”
Section: Support From Various Partiesmentioning
confidence: 99%
“…The schools can also create collaboration with Ministry of Education (MOE), Ministry of Health (MOH) and non-governmental organizations by planning and organizing campaigns and workshops for the preparation of teaching materials/aid kits, and enhance understanding and confidence of teachers, parents and children about the sexuality topic (Hasmadi et al, 2022). In addition, Venketsamy & Kinear (2020) viewed that teachers need to be empowered with knowledge and understanding of the sexuality education content so that students are more sensitive to their surroundings, make appropriate decisions, aware of sexual abuse and communicate effectively when they experience sexual abuse. Balter et al (2016) claimed that support from school administrators can increase the motivation of early childhood education teachers to talk explicitly with children about sexuality.…”
Section: Support From Various Partiesmentioning
confidence: 99%
“…The socially constructed discourse of children as sexually innocent leads to the belief that children in FP are not mature enough and, therefore, can easily be overwhelmed by the content provided in the comprehensive sexuality education curriculum (Bhana, 2016). Venketsamy and Kinear (2020) postulated that parents and teachers of young children take for granted that learners make meaning based on what they see, hear, and experience in their everyday childhood regarding societal norms and sexuality. This means that children are aware of sexuality, even if parents and teachers invalidate it.…”
Section: Children's Sexual Innocence As a Discourse In Fpmentioning
confidence: 99%
“…This could allow learners to identify and report inappropriate sexual advances and abuse at an early stage, and support the development of healthy relationships overall. Venketsamy and Kinear (2020) postulated that children only formally learn about sexuality in their teenage years, which is too late because they may have already acquired preconceived ideas about aspects of sexuality such as diverse gender identities. Children are active citizens who are aware of their bodies and feelings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2016 national prevalence study, conducted in South Africa, projects that one in three children were victims of sexual violence and physical abuse prior to them reaching the age of 18 years (Jamieson et al, 2017: 8). More recent South African research (Artz et al, 2018; Venketsamy and Kinear, 2020: 791–792) shows that child sexual abuse (CSA) is an extensive and common problem in South Africa. The Opitmus Study (South Africa) found that more boys than girls reported CSA and boys are at higher risk than girls for CSA.…”
Section: Introductionmentioning
confidence: 99%